1972
DOI: 10.1901/jeab.1972.18-295
|View full text |Cite
|
Sign up to set email alerts
|

EFFECTS OF RESPONSE‐SHOCK INTERVAL AND SHOCK INTENSITY ON FREE‐OPERANT AVOIDANCE RESPONDING IN THE PIGEON1

Abstract: Two experiments investigated free-operant avoidance responding with pigeons using a treadle-pressing response. In Experiment I, pigeons were initially trained on a free-operant avoidance schedule with a response-shock interval of 32 sec and a shock-shock interval of 10 sec, and were subsequently exposed to 10 values of the response-shock parameter ranging from 2.5 to 150 sec. The functions relating response rate to response-shock interval were similar to the ones reported by Sidman in his 1953 studies employin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
16
0

Year Published

1974
1974
2005
2005

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 29 publications
(44 reference statements)
4
16
0
Order By: Relevance
“…Stable key pecking was maintained in five pigeons through shock postponement, confirming and extending the results of Ferrari et al (1973). The inverse relationship between response rate and response-shock interval was similar to those obtained by Sidman (1953) I with rats pressing a bar, and by Klein and Rilling (1972) with pigeons pressing a treadle. This similarity in functions indicates that the characteristics of the response may be important as far as shaping avoidance behavior is concerned.…”
Section: Discussionsupporting
confidence: 84%
“…Stable key pecking was maintained in five pigeons through shock postponement, confirming and extending the results of Ferrari et al (1973). The inverse relationship between response rate and response-shock interval was similar to those obtained by Sidman (1953) I with rats pressing a bar, and by Klein and Rilling (1972) with pigeons pressing a treadle. This similarity in functions indicates that the characteristics of the response may be important as far as shaping avoidance behavior is concerned.…”
Section: Discussionsupporting
confidence: 84%
“…Todorov et al found that the longer the responseshock interval, the lower the response rate. This relationship has also been reported for an unprepared lever response with rats (Sidman, 1953) and for an unprepared treadle response with pigeons (Klein and Rilling, 1972).…”
supporting
confidence: 75%
“…In addition to noncriterion responses made with the feet to the treadle itself, many responses were made with feet, wings, and beak to the box from which the treadle extended. Klein and Rilling (1972) also observed rapid sequences of treadle pressing in pigeons. It seems likely, therefore, that altering force and excursion requirements, and possibly the dimensions of the treadle apparatus, would affect the rate of responding to the treadle.…”
Section: Discussionmentioning
confidence: 76%